Income inequality and health: Lessons from a refugee residential assignment program - Hans Grönqvist; Per Johansson; Susan Niknami (Institute for the Study of Labor (IZA), 2012)
This paper examines the effect of income inequality on health for a group of particularly disadvantaged individuals: refugees. Our analysis draws on longitudinal hospitalization records coupled with a settlement policy where Swedish authorities assigned newly arrived refugees to their first area of residence. The policy was implemented in a way that provides a source of plausibly random variation in initial location. The results reveal no statistically significant effect of income inequality on the risk of being hospitalized. This finding holds also for most population subgroups and when separating between different types of diagnoses. Our estimates are precise enough to rule out large effects of income inequality on health.
urn:nbn:de:101:1-201301212176
Keywords: I10; J15; 330; income inequality; immigration; quasi-experiment; Einkommensverteilung; Gesundheit; Flüchtlinge; Soziale Integration; Schweden